One-step, low-temperature fabrication of CdS quantum dots by watermelon rind: a green approach - Lakshmipathy R (Dove Medical Press, 2015)
Rajasekhar Lakshmipathy,1 Nallani Chakravarthula Sarada,2 K Chidambaram,3 Sk Khadeer Pasha3 1Centre for Material Science, KCG College of Technology, Chennai, Tamil Nadu, India; 2Environmental and Analytical Chemistry Division, 3Material Physics Division, School of Advanced Sciences, VIT University, Vellore, Tamil Nadu, India Abstract: We investigated the one-step synthesis of CdS nanoparticles via green synthesis that used aqueous extract of watermelon rind as a capping and stabilizing agent. Preliminary phytochemical analysis depicted the presence of carbohydrates which can act as capping and stabilizing agents. Synthesized CdS nanoparticles were characterized using UV-visible, Fourier transform infrared spectroscopy, X-ray diffraction, EDX, dynamic light scattering, transmission electron microscopy, and atomic force microscopy techniques. The CdS nanoparticles were found to be size- and shape-controlled and were stable even after 3 months of synthesis. The results suggest that watermelon rind, an agro-waste, can be used for synthesis of CdS nanoparticles without any addition of stabilizing and capping agents. Keywords: green synthesis, nanoparticles, biomimetic, atomic force microscopy